Truth-Functional Logic and the Form of a Tractarian Proposition - Oliver Thomas Spinney (Public Reason, 2022)
In this paper I argue against Michael Morris’ claim, that the Tractatus view involves holding that the possibility of truth-functional combination is prior to the possibility for sentential constituents to combine with one another. I provide an alternative interpretation in which I deny the presence of any distinction in the Tractatus between these two possibilities. I then turn to Adrian Moore’s ‘disjunctivist’ account of sentencehood, itself inspired by the Tractatus view. I argue that Moore’s account need not involve a commitment to the kind of priority Morris describes, and that it need not involve a commitment to transcendental idealism.